The leading indicators of currency crises, the case of Turkey - Alphan, Kıvanç (My University, 2002)
Turkey had faced two major crises in the periods between 1989 and 2001. These sudden collapses of the currency had dramatic consequences in the economy. The aim of this thesis is to predict the leading indicators of the crises that had occurred in this period. First the behavior of the variables is examined whether there is abnormal behavior in the crisis times and then the Signal Approach model is implemented to estimate the likelihood of a crisis by using the information by the selected macroeconomic variables. To identify the crisis periods a crisis index is constructed. The performance of the indicators is assessed individually as well as jointly. Then again by using the selected variables I have estimated the volatility of the macroeconomic variables and searched for whether there is a casualty between the variables and the crisis index. The results are striking since most of the variables used in the Signals Approach performed well and the causality between the macroeconomic indicators and the crisis index is significant at conventional levels.

Türkiye 1989-2001 dönemi içinde iki büyük kriz geçirmiştir.Bu yaşanan para krizlerinin ekonomi üzerinde çok büyük etkileri olmuştur. Bu tezin amacı sözkonusu dönemde yaşanan krizleri Signal Approach modelini kullanarak tahmin etmeye ve krize neden olan makroekonomik indikatörleri araştırmaktır.Bu amaç doğrultusunda öncelikle kriz zamanları ve diğer zamanlar arasında incelenen değişkenlerin anormal bir davranış sergileyip sergilemedikleri araştırılmıştır. Bunun için öncelikle kriz zamanlarını doğru olarak bulmak amacıyla bir endeks oluşturulmuş, daha sonra da değişkenlerin krizi tahmin etmedeki başarısı ekonometrik ve istatiksel olarak araştırılmıştır. Sonrasında ise modelde kullanılan değişkenlerin ve sözkonusu kriz endeksinin volatilite ölçümleri yapılmıştır. Bu ölçümler yardımıyla kriz endeksi ve makroekonomik değişkenler arasında bir nedensellik sınaması gerçekleştirilmiştir.
Keywords: Ekonomi_Türkiye